NIR‐Activated Multimodal Photothermal/Chemodynamic/Magnetic Resonance Imaging Nanoplatform for Anticancer Therapy by Fe(II) Ions Doped MXenes (Fe‐Ti3C2). Issue 33 (5th July 2021) - Wu, Yizhang; Song, Xueru; Xu, Wei; Sun, Kuo‐yang; Wang, Zhaokun; Lv, Zhongyang; Wang, Yue; Wang, Yong; Zhong, Wei; Wei, Jia; Cai, Hong‐Ling; Wu, Xiaoshan
Abstract: 2D MXene, Ti3 C2 (TC), has displayed enormous potential in applications in photothermal therapy (PTT), attributing to its biocompatibility and outstanding photothermal conversion capability. However, some tumor ablations are difficult to be realized completely by monotherapy due to the essential defects of monotherapy and intricate tumor microenvironment (TME). In this work, the appropriate doped Fe 2+ ions are anchored into the layers of 2D ultrathin TC nanosheets (TC NSs) to synthesize a novel multifunctional nanoshell of Fe(II)‐Ti3 C2 (FTC) through interlayer electrostatic adsorption. FTC possesses superior photothermal conversion efficiency (PTCE) than TC NSs, attributing to the enhanced conductivity promoted by interlaminar ferrous ion‐channels. Moreover, Fenton reaction based on ferrous ions endows FTC the abilities of reactive oxide species (ROS) releasing and glutathione (GSH) suppression triggered by near‐infrared (NIR) laser, featuring splendid biocompatibility and curative effect in hypoxic TME. Meanwhile, magnetic resonance imaging (MRI) responding in FTC reveals the potential as an integrated diagnosis and treatment nanoplatform. FTC could provide new insights into the development of multimoded synergistic nanoplatform for biological applications, especially breaking the shackles of MXenes merely used as a photo‐thermal agent (PTA), adopting it to bioimaging sensor and drug loading. Abstract : Near‐infrared (NIR) activated multimodal nanoplatform Fe‐Ti3 C2 (FTC) is developed by electrostatic adsorption between Ti3 C2 and Fe(II). FTC can generate reactive oxygen species (ROS) and suppress glutathione (GSH) under NIR excitation. FTC has the superior photothermal performance than Ti3 C2 . The ferrous ions also endow FTC the ability to serve as a T 1 and T 2 dual‐responding magnetic resonance contrast agent.